PENGARUH RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PERBANKAN - Bosar Hasibuan (EQUILIBIRIA, 2015)
Capital Adequacy Ratio, Non Performing Loan, Operating Expenses Operating Income Against andthe Loan to Deposit Ratio, the banking performance is measured by Return on Assets. The approachused in the quantitative approach. The population in this study that the financial statements arepublished RB Banda Raya which includes Balance Sheet, Total Assets and Income Statement whichcontain financial ratio Capital Adequacy Ratio, Non Performing Loan, Operational Costs AgainstOperating income, Loan to Deposit Ratio, and Return On Assers. while the sample in this study wasthe period of the financial statements of RB Banda Raya, published quarterly period 2008-2012. Themethod used in this study is a multiple linear regression analysis to test the hypothesis that the t testand F test using SPSS 16. Results of this study indicate that the independent variable CAR, NPL, andLDR does not significantly affect the ROA because the significance value is above 0.05, while theindependent variables significantly influence ROA, because the significance value less than 0.05.Based on R ² test showed that describes the ability of the independent variables on the dependentvariable is the ROA of 59.4% while the remaining 40.6% is influenced by other factors beyond theindependent factors used in this research.